Influence of index properties on shape of cyclic strength curve for clay-silt mixtures. Issue 102 (November 2017) - Ajmera, Beena; Brandon, Thomas; Tiwari, Binod
Abstract: Failures initiated in clay layers during recent earthquakes have emphasized the need to understand the cyclic behavior of clays. To systematically study the cyclic behavior, seventeen soils, prepared as mixtures of kaolinite and montmorillonite with quartz, and twelve natural soils were tested in a cyclic simple shear device. Cyclic strength curves were developed for 2.5%, 5% and 10% double amplitude shear strains. These curves were used to examine the influence of mineralogical composition, plasticity characteristics and shear strain on the cyclic resistance of the mixtures. A power function was used to represent the cyclic strength curves. Based on the results of this study, the mixtures were found to become increasingly resistant to cyclic loading as the plasticity index increased. Moreover, the soils with montmorillonite as the clay mineral were noted to have consistently higher cyclic resistance than the soils with kaolinite as the clay mineral. By examining the power functions, it was found that the cyclic strength curve became increasing flatter as the plasticity index increases in soils having kaolinite as the clay mineral. However, the opposite trend is observed in soils having montmorillonite as the clay mineral. The results presented in the literature for 37 soils were compared with those obtained in this study and found to be in good agreement. Highlights: 17 mineral mixtures were tested in a cyclic simple shear to study their cyclic behavior. Cyclic strength curves at different double amplitude shear strains are presented. Soils were increasingly resistant to cyclic loading as plasticity index increased. Greater cyclic resistance in soils containing montmorillonite instead of kaolinite. Curvature of cyclic strength curve depends on mineralogical composition of soils.